2015
DOI: 10.1186/s12970-015-0089-4
|View full text |Cite
|
Sign up to set email alerts
|

21 days of mammalian omega-3 fatty acid supplementation improves aspects of neuromuscular function and performance in male athletes compared to olive oil placebo

Abstract: BackgroundOmega-3 polyunsaturated fatty acids (N-3) are essential nutrients for human health and integral components of neural tissues. There is evidence that N-3 supplementation may benefit exercise performance, however, no study has investigated the ergogenic potential of N-3 supplementation. Our objective was to determine the effect of short-term N-3 supplementation on neuromuscular-function and physical-performance in well-trained athletes.MethodsMale athletes (n = 30), 25 years (SD 4.6), training 17 h.wk−… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 29 publications
4
36
0
3
Order By: Relevance
“…The countermovement jump in this case relies on the influence of the stretchshortening cycle, as well as the contractile machinery and therefore, changes in neural factors are likely to have a compounding effect on performance. With the current data showing an immediate protective effect in the High group, it is therefore possible that supplementation allowed for greater voluntary activation, a suggestion supported by Lewis et al (2015). In their study, although their findings were not in relation to EIMD, Lewis and , despite no statistical differences between groups, large effect sizes were noted (0.14 and 0.31, respectively).…”
Section: Discussionmentioning
confidence: 48%
“…The countermovement jump in this case relies on the influence of the stretchshortening cycle, as well as the contractile machinery and therefore, changes in neural factors are likely to have a compounding effect on performance. With the current data showing an immediate protective effect in the High group, it is therefore possible that supplementation allowed for greater voluntary activation, a suggestion supported by Lewis et al (2015). In their study, although their findings were not in relation to EIMD, Lewis and , despite no statistical differences between groups, large effect sizes were noted (0.14 and 0.31, respectively).…”
Section: Discussionmentioning
confidence: 48%
“…This is further supported by a series of convincing studies demonstrating enhanced neural and body mass development in preterm infants supplemented with DHA [93], [94], [95], [96], [97]. Although the precise mechanisms for such development is unclear, Lewis et al [88] demonstrated enhanced neuromuscular development after 21 days of n-3 PUFA supplementation during exercise training and the authors proposed this may have been caused by increased acetylcholine concentration and acetylcholinesterase activity at the neuromuscular junction. However, this theory was derived from an animal study [98] therefore comparing this to dynamics of human skeletal muscle makes the theory quite speculative.…”
Section: Neuromuscular Functionmentioning
confidence: 89%
“…As mentioned above, supplementation with n-3 PUFA for 150 days has been reported to enhance strength [27] and also neuromuscular recruitment following exercise training programmes [88]. The main acid thought to be responsible for this is DHA as it is the essential constituent of neuronal membrane phospholipids [88], [89] and thus considered fundamental for development of normal brain function and neuronal pathways [90].…”
Section: Neuromuscular Functionmentioning
confidence: 96%
See 1 more Smart Citation
“…However, results from our recent study, where increases in strength following omega-3 fatty acid supplementation were ~2-fold greater than the gain in muscle volume [78], provide at least some circumstantial evidence for an omega-3 fatty acid-induced improvement in muscle quality. Additionally, omega-3 fatty acid supplementation has been reported to improve neuromuscular function [85, 86] and reduce intermuscular fat infiltration [78], both of which help determine muscle quality and have been implicated in aging-induced declines in muscle function [37, 38, 3234]. Changes in other factors that influence muscle quality such as muscle architecture [31], and fibrosis [35, 36] have to the author’s knowledge not been examined in response to omega-3 fatty acids.…”
Section: Omega-3 Fatty Acid Intakementioning
confidence: 99%